Machine shop 1: hand and machining tools - Ylaya, Eugene S.; Parba, Calvin Y. ;Juanero, Ronilo D. (Quezon City, Philippines : Wiseman's Books Trading, Inc., 2019)
The content of this course notes should provide a good basis of machine shop theory and practices as well as general purpose of which is to make the students familiar with the machine tools, equipment, measuring instrument, machines usually used in maintenance and repair on board ship in which they may be serving in the near future.
Course Notes -- Chapter 1. safe working practices -- Chapter 2. Measuring Instruments -- Chapter 3. hand tools -- Chapter 4. Powered hand tools. -- Laboratory rules and policies -- Laboratory Activities -- Conversion of units -- Review Questions -- References.
Includes bibliographical references.
Keywords: MACHINE-SHOP PRACTICE